Brain aromatase mRNA expression in two populations of the peacock blenny Salaria pavo with divergent mating systems - Gonçalves, D. (2014)
Aromatase, the key enzyme in the conversion of androgens to estrogens, regulates the availability of these hormones in tissues and controls many physiological and behavioral processes. In fish and other vertebrates, the regulation of aromatase expression in the brain has been implicated in the modulation of male sexual and aggressive behaviors. Here, the pattern of mRNA expression of the brain aromatase isoform (encoded by the CYP19A2 gene also referred as CYP19b) was quantified at the peak of spawning season in brain macroareas from males and females of the blenny Salaria pavo originated from two populations displaying male alternative reproductive tactics but differing in their mating systems. In Trieste (Adriatic) nesting males aggressively defend nests and take the initiative in courtship and perform sexual displays more often than females while in Ria Formosa (Southern Portugal) the pattern is reversed as a result of shortage of appropriate nesting sites. Nesting males from Ria Formosa had overall higher levels of brain aromatase mRNA expression than nesting males from Trieste, suggesting a higher brain estrogen synthesis in these males. Since in some fish species exogenous estradiol administration has been shown to decrease sexual and agonistic behaviors, the higher levels of brain aromatase in Ria Formosa nesting males may explain their reduced expression of sexual and aggressive displays when compared with nesting males from Trieste. Alternatively, the higher brain aromatase levels in nesting males from Ria Formosa could be a mechanism to decrease the putative androgen-induced activation of aggressive and sexual displays by reducing the local availability of androgens through their metabolization into estrogens. Although females and parasitic female-like males also differ in their displays between populations, the interpopulational pattern of brain aromatase mRNA expression was similar, suggesting that other neuroendocrine agents mediate the expression of female and female-like behaviors. In conclusion, brain aromatase availability seems like a probable mechanism to regulate the effects of steroids on the brain circuits underlying the expression of sexual and agonistic displays in S. pavo.